2017
DOI: 10.7759/cureus.1396
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Ki-67 Index, World Health Organization Grade and Patient Survival in Glial Tumors With Astrocytic Differentiation

Abstract: BackgroundGlioblastoma multiforme (GBM) is a class IV astrocytic tumor, the most malignant of the four groups of World Health Organization (WHO) tumors with astrocytic differentiation.AimThe aim of this study was to estab­lish whether a correlation exists between the Ki-67 index of tumors with astrocytic differentiation, WHO grade, and patient survival.Materials and methodsA retrospective non-clinical approach to patient selection was chosen for the aim of the study. A total of 47 patients diagnosed and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…The precise morphological features extracted from the most aggressive regions help to investigate intratumoral histological heterogeneity for precise histopathology grading (Walker et al, 2001). The primary grading results still support the conclusion that the only sure way to determine the histopathological WHO grade remains the pathohistological evaluation of the H&E stained tumor sample (Stoyanov et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…The precise morphological features extracted from the most aggressive regions help to investigate intratumoral histological heterogeneity for precise histopathology grading (Walker et al, 2001). The primary grading results still support the conclusion that the only sure way to determine the histopathological WHO grade remains the pathohistological evaluation of the H&E stained tumor sample (Stoyanov et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…Çalışmamız da mitoz sayısı ve Ki-67 indeksi arasında olumlu, orta derecede korelasyon bulduk. Bu bulgumuz literatür ile uyumludur (4,5). Palizatlaşan hücre nekrozu GBM'nin patolojik karakteristik özelliklerinden birisidir.…”
Section: Gereç Ve Yöntemunclassified
“…Ki-67 pozitif hücrelerinin oranı Ki-67 proliferasyon indeksini belirler. Literatürde, Ki-67 fraksiyonunun yüksek olduğu glial tümörlerin daha agresif seyrettiğine dair birçok çalışma mevcuttur (5,6). Diğer yandan, iskemik strok veya subaraknoid kanama gibi intrakraniyal patolojilerde platelet volüm indeksi (PVİ) ve prognoz ile ilgili yayınlarda artış görülmektedir.…”
Section: Introductionunclassified
“…The Ki-67 proliferation index increases in malignant cells (15). Previous studies have shown the correlation between Ki-67 and brain tumor malignancy class is useful in the evaluation of clinical course and patient outcome (16,17).…”
Section: Introductionmentioning
confidence: 99%